2013
DOI: 10.2514/atcq.21.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Metrics to Characterize Airport Operational Performance Using Surface Surveillance Data

Abstract: Detailed surface surveillance datasets from sources such as the Airport Surface Detection Equipment, Model-X (ASDE-X) have the potential to be used for the analysis of airport operations, in addition to their primary purpose of enhancing safety. This paper describes how surface surveillance data can be used to measure airport performance characteristics in three different ways: (1) Characterization of surface flows, including identification of congestion hotspots, queue dynamics and departure throughput; (2) D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
4
1
0
Order By: Relevance
“…Figure 10 shows the three-dimensional contour plot of the dependencies of the throughput Q on the distribution probability a and the interval of arrival time T in . It was observed that throughput Q gets sluggish and reaches the plateau as T in increases, thus making a type of sigmoid curve, the tendency of which is similar to the experimental data of the same type of systems in previously reported works [25][26][27]. On the other hand, the dependence of throughput Q on arrival time interval T in does not reach the plateau in between 4 and 2min at around where the parameter α gets close to the ratio of the number of parking sites in the domestic route to that in the whole system.…”
Section: Analysis With the Classical M M C Queuesupporting
confidence: 85%
See 1 more Smart Citation
“…Figure 10 shows the three-dimensional contour plot of the dependencies of the throughput Q on the distribution probability a and the interval of arrival time T in . It was observed that throughput Q gets sluggish and reaches the plateau as T in increases, thus making a type of sigmoid curve, the tendency of which is similar to the experimental data of the same type of systems in previously reported works [25][26][27]. On the other hand, the dependence of throughput Q on arrival time interval T in does not reach the plateau in between 4 and 2min at around where the parameter α gets close to the ratio of the number of parking sites in the domestic route to that in the whole system.…”
Section: Analysis With the Classical M M C Queuesupporting
confidence: 85%
“…In the case of 2 min, an important observation was made; the throughput Q reduces after α reaches the maximum capacity. The overall reduction of throughput Q in between 0.6 and 1.0 seems to be unique because the throughput plateaus after saturation, in similar systems [25][26][27]. Besides, we confirmed from figure 5 that the existence of the delay of staying time is not the critical factor for the overall reduction because we observe it in both cases: with stochastic and with deterministic parameters.…”
Section: Simulation Resultssupporting
confidence: 65%
“…Figure 9 shows the three-dimensional contour plot of the dependencies of the throughput Q on the distribution probability α and the interval of arrival time T in . It was observed that throughput Q gets sluggish and reaches the plateau as T in increases, thus making a type of sigmoid curve, the tendency of which is similar to the experimental data of the same type of systems in previously reported works [27,28,29]. On the other hand, the dependence of throughput Q on arrival time interval T in does not reach the plateau in between 4 and 2 min at around where the parameter α gets close to the ratio of the number of parking sites in the domestic route to that in the whole system.…”
Section: Discussion For Future Worksupporting
confidence: 85%
“…In the case of 2 min, an important observation was made; the throughput Q reduces after α reaches the maximum capacity. The overall reduction of throughput Q in between 0.6 and 1.0 seems to be unique because the throughput plateaus after saturation, in similar systems [27,28,29]. Besides, we confirmed from Fig.…”
Section: Simulation Resultssupporting
confidence: 70%
“…It uses real-time tracking of aircraft on the surface to detect potential conflicts and to monitor conformance. There is potential, however, to use the data generated by it for surface operations analysis [23], [24] and modeling of aircraft behavior. Reported parameters in ASDE-X include the position, velocity, altitude and heading of each aircraft.…”
Section: Related Workmentioning
confidence: 99%